Design and Implementation of an IoT-Based Speed Control and Monitoring System for 3-Phase Induction Motors - Fanani, Wisnu Bachtiar; Kustanto, Jaka Septian; Setiawan, Hadi; Edy Kristiyono, Antonius (Nusantara Publisher, 2025)
As industries seek to improve product quality and reduce costs, automation tools like 3-phase induction motors have become indispensable due to their simplicity, cost-effectiveness, efficiency, and ease of maintenance. This study investigates the automation of monitoring for 3-phase induction motors through the integration of various components, including the A3114 Hall Effect sensor, PZEM-PP4T sensor, 20x4 LCD, ESP32 module, relay, Mitsubishi D700 inverter, and MCP 4725 sensor. Testing results show high accuracy in measuring critical motor parameters such as speed, voltage, and current. The Hall Effect sensor demonstrated an average accuracy of 4.12% compared to a tachometer, while the PZEM sensor exhibited a 0.90% accuracy for voltage and a 0.98% accuracy for current when compared to a multimeter, affirming the reliability of the system. Overall, the system provides consistent and precise measurements, transforming manual monitoring into an efficient automated process. This advancement significantly enhances the reliability and effectiveness of 3-phase motor monitoring in industrial applications